Influencia de las estrategias cognitivas de regulación emocional sobre la ansiedad y depresión en universitarios: análisis preliminar - Dominguez-Lara, Sergio (2017)
ABSTRACT Objective: Determine the influence of cognitive emotion regulation strategies on anxiety and depression in college students Material and methods: This research was conducted on a sample of 127 individuals (69.3 % women) between ages 18 and 57 years old. Was implemented a regression multiple analysis on anxiety (GAD-2) and depression (PHQ-2), with the subscales of CERQ as predictors. Results: In both cases, predictors explain high variability of the criteria (R 2 > 50 %). Cognitive strategies rumination and catastrophizing predicted anxiety; Positive Reinterpretation and catastrophizing and predict positively and negatively, respectively form, depression. Conclusions: The influence of cognitive emotion regulation strategies on anxiety and depression is significant. The practical consequences and limitations are discussed.